Waiting for my sentence: Air pollution and the productivity of court rulings - Luis Sarmiento (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
I assert that air pollution from nitrogen oxides affects the productivity of employees in Mexican court hearings. This is the first article analyzing this connection and the first to disentangle work-breaks from the productivity of white-collar workers. I merge hourly pollution with granular hearing data under the assumption that the length of the hearing approximates productivity and identify causality from panel and instrumental variable techniques. Results show a loss of 3.83 workdays during the sample period due to the productivity shock stemming from comparing exposure at the hours with the highest and lowest concentration of nitrogen oxides in the data-set.
Keywords: C23; J24; Q53; 330; air pollution; nitrogen oxides; productivity; labor market effects